UK survey of non-medical use of prescription drugs (NMURx) as a valuable source of general population illicit drug use data. Issue 1117 (11th January 2019) - Ng, Fu Liang; Rockhill, Karilynn; Black, Joshua; May, Kevin Patrick; Whittington, Melanie D; Wood, David M; Dargan, Paul I; Green, Jody L
Abstract : Purpose of study: The aim of the study is to describe the prevalence of illicit drug use in England and Wales using data from the UK Survey of Non-Medical Use of Prescription Drugs (NMURx) programme and to compare against the well-established Crime Survey England and Wales (CSEW). The rationale is that recreational and illicit drug use is common, but the prevalence is difficult to estimate with personal interviewing methods. Study design: We compared two cross-sectional population surveys (NMURx, n=8903 and CSEW, n=20 685) with data regarding self-reported recreational drug use and demographics. NMURx is an online survey using non-probability sampling methodology with preset demographical quotas based on census data. CSEW surveys drug use via computer-assisted self-interviewing as part of a computer-assisted personal-interviewing crime survey. Results: Cannabis was the most frequently used drug regardless of demographics. Prevalence of drug use for specific substances was generally higher for males, younger ages and students. The relationship between income and drug misuse is less clear. Self-reported prevalence of drug use in the NMURx survey is consistently higher than CSEW (absolute difference 1%–3 % across substances and timescales) and persists after stratification for gender, age, student status and household income. Conclusions: The NMURx survey has a broad reach of participants, and a sampling scheme that achieves external validity, compared with general population demographics. NMURx's online format allows flexibility in items surveyed and in response to emerging trends. The self-reported drug use in the NMURx cohort is comparable, although slightly higher, than the CSEW estimates.